A influência da mata nativa na diversidade e abundância de abelhas polinizadoras de cajueiros (Anacardium occidentale L.) em plantios comerciais - Rocha, Epifânia Emanuela de Macêdo (2013)
This study aimed to understand the abundance, diversity and frequency of bees visiting flowers in cashew tree growing areas near and far from commercial native forest. The research was conducted during the blooming season in 2012, from August to November in commercial orchards in the city of Horizonte, Ceará. The methodology consisted in marking five different gradients of distance (40m, 80m, 120m, 160m and 200m) in all 10 areas to perform and record count of floral visitors in 500 panicles during transect conducted at six different times (7h, 9h, 11h, 13h, 15h and 17h), and captured with an insect net in six selected trees, five minutes at each cashew tree in an area of 25m x 50m. We collected 368 flower visitors among social bees (331), solitary bees (21) and other species (16) floral visitors in panicles of cashew. The relationship between insect abundance and time of collection reveals that for all bees collected, the hours of 7h and 9h of the morning were those with the greatest abundance of insects visiting the flowers of cashew mainly of stingless bees. The frequency of flower visitors in 500 cashew flowering panicles in the months, both in areas with native vegetation as no native forest, did not vary according to the period of flowering (p>0.05), just as there was no significant difference (p>0.05) in the mean number of bees compared the different distances during the counts in areas with native forest fragment and native forest without. Social bees were the most abundant group and among them 176 were Apis mellifera and 159 stingless bees. Solitary bees were poorly represented and Centris spp. and Xylocopa (Neoxylocopa) cearensis were seen only in a few areas showing no significant effect (p>0.05) on the site (with or without native forest), area, time and day of collection. We conclude from this study that the presence of native forest fragment near the edge of culture, did not influence the abundance of floral visitors on selected distances, however the existence of remnant native forest near the cashew trees, allowed to remain in social bees growing areas during the flowering period, mainly at times when the flowers of cashew are more receptive to pollination.